2000
DOI: 10.1046/j.1440-1754.2000.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

True hermaphroditism

Abstract: The management of true hermaphroditism is controversial and requires a multidisciplinary approach. It has many implications for both the parent and child. We discuss the issues involved for the patients and their parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
2
10
0
2
Order By: Relevance
“…The most common karyotype was 46,XX, constituting 61.6% of patients in the present study and reviewed cases from Japan. This finding was consistent with the published literature from other countries 2,3,11 . A large review of ovotesticular DSD has shown geographic variations 3 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The most common karyotype was 46,XX, constituting 61.6% of patients in the present study and reviewed cases from Japan. This finding was consistent with the published literature from other countries 2,3,11 . A large review of ovotesticular DSD has shown geographic variations 3 .…”
Section: Discussionsupporting
confidence: 92%
“…The female : male ratio as the sex of rearing was 1:1 in the present study, similar to findings from a previous review 3,11 . Surgery is generally necessary after gender assignment.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations